OCCURRENCE AND CLINICAL EVOLUTION OF NEUROPATHIC DYSESTHETIC PAIN IN MULTIPLE SCLEROSIS (2-YEAR PROSPECTIVE STUDY) - Delva, M.Yu.; Skoryk, K.S.; Delva, I.I. (World of Medicine and Biology, 2023)
The occurrence and evolution of neuropathic dysesthetic pain in patients with multiple sclerosis during a 2-year observation period was studied. 241 patients were included in the study. Dysesthetic pain was diagnosed using the PainDETECT questionnaire. Patients with newly detected (recurrent) dysesthetic pain were examined at the beginning of the study, after 1, 3 and 6 months depending on the duration of the pain. Over a 2-year period, the cumulative risk of dysesthetic pain was 15.6 % (11.4 %–21.0 %), and the cumulative risk of recurrence was 8.8 % (3.0 %–23.0 %). The first detected (recurrent) dysesthesia lasted more than 3 months in two-thirds of cases. The first detected (recurrent) dysesthesia was mainly localized in the lower back and lower limbs. Patients described dysesthesia both at the time of its occurrence and later, indicating more than 2 descriptors (most often “burning”, “freezing” and “tingling”). The chronicity of dysesthetic pain was associated with the expansion of pain areas, with the transformation of the pain pattern (from pain attacks to constant pain), with a decrease in pain intensity.
Keywords: multiple sclerosis; neuropathic dysesthetic pain; occurrence; clinical evolution